Two new softnose skates of the genus Brochiraja (Rajoidei: Arhynchobatidae) from the deepwater slopes and banks of the Norfolk Ridge (South-West Pacific) - Last, Peter R.; Séret, Bernard (Zootaxa, 2012)
Two new species of the softnose skate genus Brochiraja are described based on material collected from the Norfolk Ridgein the northern Tasman Sea (South-West Pacific). Most of this material was collected in 2003 by the New Zealand vessel,RV Tangaroa, during the NORFANZ voyage. These species extend the known range of the genus northward along theNorfolk Ridge, and along with B. aenigma, are the only other representatives of the genus found outside seas adjacentNew Zealand. Brochiraja heuresa sp. nov. is known from the western Norfolk Ridge and the Wanganella Bank at 870–1350 m depth, whereas B. vittacauda sp. nov. is known from a smaller area of the western Norfolk Ridge at 629–973 mdepth. These species differ from each other, and from other nominal members of the genus, in morphometrics, meristics, coloration and squamation.